Analisa Dan Perancangan Portal Puskesmas Manado Kota Cerdas - Mangamba, Yunifer; Sentinuwo, Steven R.; Karouw, Stanley (Jurnal Teknik Informatika, 2020)
Abstract — Pusat Kesehatan Masyarakat (Puskesmas) is one of the closest public health service facilities to the community. The Puskesmas is the technical implementing unit of the district / city office which is responsible for carrying out health development in an area. To maximize the process of Puskesmas services in the community, it is necessary to be supported by the implementation of information technology by using the Manado Smart City as supporting media for Puskesmas services through information. The purpose of this study is to create a health center portal application Manado smart city. The application development method used is Rapid Application Development (RAD). Analysis and design of the puskesmas portal conducted in the city of Manado to identify puskesmas needs and community need to further improve services to the community which is supporting improvement in access to and the quality of health services in the community aimed at realizing a community that has healthy behaviors that include an awareness of the will and ability to live a healthy life. The results of the analysis and design of the puskesmas portal were able to help developers more easily build the smart city puskesmas portal to overcome the problems that occur in each health center. Keywords — Design System; Information System; Portal Public Health Center; Smart City ManadoPusat kesehatan masyarakat (Puskesmas) adalah salah satu sarana pelayanan kesehatan masyarakat yang paling dekat dengan masyarakat. Puskesmas sebagai unit pelaksana teknis dinas kabupaten/kota yang bertanggungjawab menyelenggarakan pembangunan kesehatan di suatu wilayah. Untuk memaksimalkan proses-proses pelayanan Puskesmas di masyarakat perlu di dukung oleh implementasi teknologi informasi dengan penggunaan Portal Puskesmas Manado Kota Cerdas sebagai media pembantu pelayanan puskesmas melalui informasi yang mempermudah masyarakat. Tujuan penelitian ini adalah menghasilkan perancangan aplikasi portal puskesmas manado kota cerdas. Metode pengembangan aplikasi yang dipakai adalah Rapid Application Development (RAD) . Analisa dan perancangan portal puskesmas yang dilakukan di kota Manado untuk mengidentifikasi kebutuhan puskesmas dan kebutuhan masyarakat untuk lebih meningkatkan pelayanan ke masyarakat yaitu mendukung meningkatkan akses dan mutu pelayanan kesehatan pada masyarakat yang bertujuan mewujudkan masyarakat yang memiliki perilaku sehat yang meliputi kesadaran kemauan dan kemampuan hidup sehat. Hasil dari Analisa dan perancangan portal puskesmas mampu membantu pengembang lebih mudah membangun portal puskesmas manado kota cerdas. Hasil dari penelitian saya adalah perancangan portal puskesmas untuk mengatasi permasalahan yang terjadi di setiap puskesmas Kata Kunci: Desain system; Manado Kota Cerdas; Portal Puskesmas; Sistem informasi.